Severe Progressive Multifocal Leukoencephalopathy (PML) and Spontaneous Immune Reconstitution Inflammatory Syndrome (IRIS) in an Immunocompetent Patient - Krey, Lea; Raab, Peter; Sherzay, Romilda; Berding, Georg; Stoll, Matthias; Stangel, Martin; Wegner, Florian (Frontiers in Immunology, 2019)
Background: Progressive multifocal leukoencephalopathy (PML) is an opportunistic infection with JC-virus (JCV), a papova-virus, affecting mostly oligodendrocytes and the white matter of the central nervous system. PML almost exclusively occurs in immunocompromised patients based on different underlying conditions of severe cellular immunodeficiency such as HIV/AIDS, secondary to neoplastic and autoimmune diseases, or during immunosuppressive therapy. Case presentation: We present the case of an otherwise healthy and immunocompetent patient without immunosuppressive therapy who was admitted with hemianopsia to the right side, sensory aphasia and changes of behavior. Magnet resonance imaging (MRI) and laboratory testing confirmed the diagnosis of PML, although functional tests did not show any evidence for cellular immunodeficiency. Extensive immunological tests did not reveal an apparent immunodeficiency. During symptomatic therapy the patient developed seizures which were assumed to be caused by a spontaneous immune reconstitution inflammatory syndrome (IRIS) demonstrated by MRI. We added a high dose of intravenous corticosteroids to the antiepileptic treatment and seizures ended shortly thereafter. However, the impairments of vision, behavior and language persisted. Conclusions: Our case report highlights that an apparently immunocompetent patient can develop PML and IRIS spontaneously. Therefore, MRI should be applied immediately whenever a rapid progression of PML symptoms occurs as treatment of IRIS with corticosteroids can result in a marked clinical improvement.